SISTEM PEMASARAN GIFT ENVELOPE BERBASIS WEBSITE PADA HOME INDUSTRI FALAH (Information Technology and Telematics, 2013)
Currently, found many home industries engaged in the craft have limited marketing strategy and still use the manual method, has not exploit the internet as a marketing strategy. The importance of developing a marketing ploy than a manual system into an e-marketing is a solution that can help home industry in developing marketing strategies in order to achieve a greater market share than ever before. The purpose of this article is analyzed the existing marketing process, then designing strategy of e-marketing and applications appropriate to be applied on the home industries. The research methodology consisted of analysis methods and design methods. The results obtained based on research is an application of e-marketing based on the analysis and observation, where the application contains information about products, bookings and promotions. Keywords: E-marketing, Marketing, Internet.